Physiological and Metabolomics Analyses Revealed That Overexpression of CBL-Interacting Protein Kinase 23 Accelerate Tuber Sprouting in Potato - Fang Zhou; Fengjuan Wang; Xing Zhang; Yifei Lu; Bi Ren; Shimin Yang; Liming Lu; Liqin Li (Horticulturae)
The potato (Solanum tuberosum L.) plays an important role in ensuring global food security. Potato tubers store abundant nutrients and are also reproductive organs. The adjustment of tuber sprouting plays a vital role in timely sowing and improving tuber product quality. CBL-interacting protein kinases (CIPKs) exert an important function in the entire life cycle of plants and in coping with stress. In our present study, we found that the StCIPK23 expression level increased during storage and that overexpression of StCIPK23 can accelerate tuber sprouting. Physiological assays indicated that overexpressing StCIPK23 altered carbohydrate metabolism and antioxidant-related enzyme activities during storage. Starch branching enzyme (SBEI) gene expression was upregulated, while sucrose synthase (SS), 3-phosphoglyceric phosphokinase (PGK), and glyceraldehyde-3-phosphate dehydrogenase 1 (GAPC1) gene expression were downregulated in StCIPK23-overexpressing potato. High gibberellin (GA) content and low abscisic acid (ABA) content were also detected in transgenic tubers. We conducted metabolomics analysis on bud eyes, and the results showed a total of 94 differential metabolites were found. Among them, 61 metabolites were increased, the top three metabolites were coumaryl alcohol, glutathione and quercetin–glucoside–glucoside–rhamnoside. Our results suggest that StCIPK23 is a positive regulator of potato tuber sprouting.